Exploring the Relationship between Consumer Knowledge and Skepticism towards Pro-Environmental Advertising: An Empirical Investigation - Lee, Jinhee; Cheong, Hyuk Jun (KOME, 2024)
This study investigates the potential impact of consumer knowledge on inclination toward skepticism about pro-environmental advertising. Using the Persuasion Knowledge Model (PKM), the research explores the intricate interplay between three facets of consumer knowledge: persuasion, agent and topic knowledge, and consumer skepticism of pro-environmental advertising. The study also examines whether individuals’ prior experience of pro-environmental advertising and eco-friendly products contribute to the development of the three dimensions of consumer knowledge. Researchers administered online surveys to a cohort of U.S. consumer panellists, and subsequently subjected the gathered data to structural equation modelling. The research found that consumers with a heightened acumen in persuasion, agent, and topic knowledge exhibit a notably diminished degree of skepticism toward pro-environmental advertising. Additionally, individuals’ antecedent interactions with pro-environmental products enhance the depth of all three dimensions, whereas prior exposure to pro-environmental advertising appears predominantly to bolster persuasion knowledge alone.